2018
DOI: 10.1097/jcp.0000000000000904
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clozapine Use and Safety by Using Comprehensive National Data From the Japanese Clozapine Patient Monitoring Service

Abstract: The data obtained in this study, particularly regarding the incidence of clozapine-induced adverse events, will enable the optimal and safe use of clozapine in Japanese patients with treatment-resistant schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 22 publications
2
34
0
3
Order By: Relevance
“…A dosing study with >3,000 samples from the Japanese clozapine database described a mean dose of 186 mg/day. [20] In a survey of 117 Indian psychiatrists, Shrivastava and Shah [21] indicated that almost all (86%) of their patients were stabilized on clozapine doses lower than 300 mg/day. A recent Asian review described clozapine daily dosing in single samples from several different countries.…”
Section: The Evidence From Clozapine Dosing In Asian Countriesmentioning
confidence: 99%
“…A dosing study with >3,000 samples from the Japanese clozapine database described a mean dose of 186 mg/day. [20] In a survey of 117 Indian psychiatrists, Shrivastava and Shah [21] indicated that almost all (86%) of their patients were stabilized on clozapine doses lower than 300 mg/day. A recent Asian review described clozapine daily dosing in single samples from several different countries.…”
Section: The Evidence From Clozapine Dosing In Asian Countriesmentioning
confidence: 99%
“…Despite its efficacy with TRS, the use of CLZ is significantly restricted by severe side effects such as CLZ-induced agranulocytosis (CIA)/CLZ-induced granulocytopenia (CIG) (CIAG), which is rare but potentially life threatening. CIAG events are observed in approximately 1% (for CIA) and 3% (for CIG) of CLZ-treatment patients, although the prevalence of CIA differs between populations (Caucasian: .3%.9%; Asian: greater than 1%; Japanese: 1.1%) (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In these models, we did not include the health state related to death and sepsis, because no case has been reported in such conditions after the CPMS started in Japan [12] or very low mortality (0.013%) based on the meta-analysis [13]. Moreover, we did not consider the possibility of CLZ discontinuation based on the WBC cutoff (<3000/mm 3 ), because this "WBC count" definition was not a common reason for discontinuation (in such cases, the ANC usually decreased to 1500/mm 3 ) [13].…”
Section: Methodsmentioning
confidence: 99%
“…The outcome included the mean cost-per-patient and QALYs-per-patient for the calculation of the ICER over a 10-year time period. In particular, in Japan, the mean age of the patients at the start of CLZ treatment was 40.6 years [12], and antipsychotics were recommended to be continued. Thus, we assumed that patients with TRS receive CLZ treatment for at least 10 years, if tolerated.…”
Section: Population Model Structure and Parametersmentioning
confidence: 99%
See 1 more Smart Citation